2022
DOI: 10.1029/2021sw002953
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Occurrence Frequency of dB/dt Spikes During Magnetic Storms 1980–2020

Abstract: One of the most prominent (and potentially dangerous) features of space weather are geomagnetically induced currents, commonly known as GICs. The understanding of GICs is a major concern in order to preserve the power and communication systems and other technology on the ground. GICs are currents induced by rapid fluctuations in the Earth's magnetic field in any extended conducting technological infrastructure and can lead to malfunction or black outs of high-voltage power transmission systems (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(71 citation statements)
references
References 67 publications
(146 reference statements)
12
45
0
Order By: Relevance
“…We first consider the results from 2016. In the case of all three magnetic components, spikes are observed near auroral latitudes of 64 to 74 • , concentrated in two main local time sectors, which we loosely refer to as pre-midnight (17 to 02 MLT) and dawn (02 to 09 MLT); these are the same "hotspots" identified by Schillings et al (2022) and previous workers. The boundaries of these MLT regions are indicated in the middle panel; we will refer to the 09 to 17 MLT sector as noon.…”
Section: Observations and Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…We first consider the results from 2016. In the case of all three magnetic components, spikes are observed near auroral latitudes of 64 to 74 • , concentrated in two main local time sectors, which we loosely refer to as pre-midnight (17 to 02 MLT) and dawn (02 to 09 MLT); these are the same "hotspots" identified by Schillings et al (2022) and previous workers. The boundaries of these MLT regions are indicated in the middle panel; we will refer to the 09 to 17 MLT sector as noon.…”
Section: Observations and Discussionsupporting
confidence: 53%
“…If we refer to a spike in any component, we use ∆B. Our method of analysis is similar to previous dB/dt studies using SuperMAG data (Rogers et al, 2020;Schillings et al, 2022).…”
Section: Observations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It transforms our traditional knowledge about the external source of ground magnetic field ULF oscillations, which considers geomagnetic ULF oscillations originally come from the solar wind or KHI along the flanks. Although several studies have shown that fewer geomagnetically induced currents are observed in the dayside than those observed in other MLTs (Engebretson et al., 2019; Schillings et al., 2022), magnetosheath HSJs are likely one important dayside driver of geomagnetically induced currents.…”
Section: Discussionmentioning
confidence: 90%
“…We also highlight the interpretation of the time derivative of the radial magnetic field dB r /dt as the radial component of the curl of the geomagnetically induced electric field (Vanhamäki et al, 2013) and present a statistical analysis of the properties of this quantity. This analysis stands in contrast to the analysis of the time derivative of the horizontal magnetic field (often denoted ∂H/∂t), which has received comparatively much more attention (Juusola et al, 2020;Tanskanen et al, 2001;Viljanen et al, 2001;Schillings et al, 2022;Weigel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%